Planting our world - Mancuso, Stefano (Other Press LLC, 2022)
"With fun, fascinating vignettes, a renowned neurobiologist illuminates the interconnectedness of plant life and how we can learn from it to better plan our communities. It all begins and ends with plants. From the chance to live on this planet to the pleasure of listening to the sound of a violin-every story begins with a plant. There's no getting around it. We animals account for a paltry 0.3% of the planet's biomass while plants add up to 85%. It is obvious, therefore, that every story on this planet has a plant as its protagonist. Our world is a green world; Earth is the planet of plants. And when, with just a little training, we are able to look at the world without seeing it solely as humanity's playground, we cannot help but notice the ubiquity of plants. They are everywhere and their stories are inevitably wound up with ours. As every tree in a forest is linked to all the others by an underground network of roots, uniting them to form a super organism, so plants constitute the nervous system, the plan that is the "greenprint" of our world. Not to see this plan, or even worse, to ignore its existence, is one of the most serious threats to the survival of our species. The brilliant neurobiologist Stefano Mancuso is back with a great book to tell us about the greenprint of our world. He does it through unforgettable stories starring plants (and it couldn't be otherwise); stories combining an inimitable narrative style and remarkable scientific rigor. From the story of the red spruce that gave Stradivarius the wood for his fourteen violins, to the Kauri tree stump, kept alive for decades by the interconnected root system of nearby trees. From the story of the slipperiness of the banana skin to the plant that solved the "crime of the century," the Lindbergh kidnapping, by way of wooden ladder rungs"--